A comparative analisys of pelvic floor muscle strength in women with stress and urge urinary incontinence - Gameiro, Monica Orsi [UNESP]; Moreira, Eliane Cristina; Ferrari, Renata Spagnoli [UNESP]; Kawano, Paulo Roberto [UNESP]; Padovani, Carlos Roberto [UNESP]; Amaro, João Luiz [UNESP] (FapUNIFESP (SciELO), 2012)
Aims: To assess pelvic floor muscle (PFM) strength in women with stress urinary incontinence (SUI) and urge urinary incontinence (UUI). Materials and Methods: 51 women were prospectively divided into two groups, according to the symptoms as SUI (G1 = 22) or UUI (G2 = 29). Demographic data, such as number of pads 24 hours, number of micturations 24 hours and nocturia, delay time of urgent void (i.e., the time period for which an urgent void could be voluntarily postponed), number of parity and vaginal deliveries were obtained using a clinical questionnaire. Objective urine loss was evaluated by 60-min. Pad Test, subjective urine stream interruption test (UST) and visual survey of perineal contraction. Objective evaluations of PFM were performed in all patients (vaginal manometry). Results: Median of age, mean number of pads 24 hours, nocturia and warning time were significantly higher in UUI comparing to SUI group. During UST, 45.45% in G1 and 3.44%, in G2, were able to interrupt the urine stream (p < 0.001). The 60-min. Pad Test was significantly higher in G2 compared to G1 women (2.7 ± 2.4 vs 1.5 ± 1.9 respectively, p = 0.049). Objective evaluation of PFM strength was significantly higher in the SUI than in the UUI patients. No statistical difference was observed regarding other studied parameters. Conclusion: Pelvic floor muscle weakness was significantly higher in women with UUI when compared to SUI.
Keywords: Pelvic floor; Stress; Urge; Urinary incontinence; Women